Macrophage populations show an M1‐to‐M2 transition in an experimental model of coronal pulp tissue engineering with mesenchymal stem cells. (28th November 2018) - Gu, B.; Kaneko, T.; Zaw, S. Y. M.; Sone, P. P.; Murano, H.; Sueyama, Y.; Zaw, Z. C. T.; Okiji, T.
Abstract: Aim: To assess M1/M2 macrophage phenotypes in a coronal pulp regeneration model in rats, under the hypothesis that there are dynamic M1/M2 phenotype changes during the different stages of the pulp regeneration. Methodology: The maxillary first molars of Wistar rats were pulpotomized, and biodegradable hydrogel‐made scaffolds carrying rat bone marrow mesenchymal stem cells were implanted in the pulp chamber. After 3, 7 and 14 days, samples were processed for (i) histological analysis and double immunoperoxidase staining for CD68 (a general macrophage marker) and one of either CCR7 (an M1 marker), CD163 (an M2 marker) or CD206 (an M2 marker); (ii) real‐time PCR for AIF1 (an M1 marker), CD163, CD206, IL‐10 and TNF‐ α mRNA expression; and (iii) Western blotting for the detection of CD68, CCR7 and CD206 proteins. Results: Histological analysis of the implanted region revealed sparse cellular distribution at 3 days, pulp‐like tissue with a thin dentine bridge‐like structure at 7 days, and dentine bridge‐like mineralized tissue formation and resorption of most scaffolds at 14 days. CCR7+ macrophages had the highest density at 3 days, and then significantly decreased until 14 days ( P < 0.05). In contrast, M2 marker (CD163 or CD206) expressing macrophages had the lowest density at 3 days and significantly increased until 14 days ( P < 0.05). AIF1 and TNF‐ α mRNA levels, and CD68 and CCR7 protein levels were highest at 3 days. CD163 and CD206 mRNA levels, and CD206 protein levels increased with time and showed the highest at 14 days. IL‐10 mRNA was highest at 3 days, decreased at 7 days and increased at 14 days. Conclusions: Macrophages in the regenerating pulp tissue underwent a distinct transition from M1‐dominant to M2‐dominant, suggesting that the M1‐to‐M2 transition of macrophages plays an important role in creating a favourable microenvironment necessary for pulp tissue regeneration.